(untitled) (Research, Society and Development, 2022)
Calcium is an important macronutrient for the agronomic performance of broccoli, and its supply via seed treatment can contribute to the initial development of plants. Considering the importance of calcium in brassica production and the possibility of improving seed quality, the objective was to evaluate the effect of treatment with this nutrient in broccoli seeds on physiological quality. Eleven treatments were evaluated [factorial with two sources (calcium nitrate and calcium chloride) versus five concentrations (0.5; 2.5; 5.0; 10.0; 25.0 g of Ca L-1 of water) + one untreated control] in a completely randomized design, with four replications. The treatment was done with the immersion of the seeds in the solutions/treatments for 30 minutes and then the seeds were dried. Germination, first germination count, germination speed index, accelerated aging, emergence and emergence speed index were evaluated. The treatment of broccoli seeds with calcium did not affect seed germination, but reduced their vigor, with a reduction in germination and emergence speed.